Gamma irradiation induced stabilisation in CuAlNi shape memory alloys - Balo, S. Nevin; Orhan, Abdulvahap (Springer, 2025)
After annealing, gamma irradiation was applied to CuAlNi shape memory alloy samples at different doses and investigated how the stabilization was affected by irradiation. Conversion temperatures and thermodynamic parameters were determined by thermal measurements. Non-regular increases in these parameters were observed depending on the irradiation dose. Depending on the irradiation dose, the structural analyzes of the alloy samples were made with X-ray diffraction. The changes in microhardness and crystallite size of the alloy samples with increasing irradiation dose were investigated. The crystallite size tends to decrease with increasing irradiation dose, and the increase in microhardness favors the change in crystallite size. In results are discussed to the stabilization of martensite by increased irradiation dose in CuAlNi alloys.
Keywords: CuAlNi Shape memory alloys; gamma- radiation; Martensitic transformation; Crystallite size